Creation Of Anti Stomatitis-S Gel in The Treatment Of Stomatits In Children (Texas Journal of Medical Science, 2024)
The most urgent problem of dentistry is diseases of the oral mucosa, both in adults and in children of all age groups. The oral cavity is an environment with a high potential for the development of inflammatory processes, since the mucous membranes are attacked by microorganisms in the first place. Stomatitis is a disease of the oral mucosa that occurs with an inflammatory reaction, which is characterized by all the classic signs of inflammation. The study of treatment methods is an integral factor in the development of relapses and the formation of chronic stomatitis in children